The brain dynamics of trust decisions and outcome evaluation in narcissists - Guo, Fengbo; Yang, Ziyang; Liu, Tengfei; Gu, Li (Frontiers in Psychology, 2022)
Individuals with narcissism are, by definition, self-centered, focus on self-benefit, and demonstrate less prosocial behaviors. Trusting strangers is risky, as it can result in exploitation and non-reciprocation. Thus, trust may be antagonistic to narcissism. However, how narcissists make the choice to trust remains to be elucidated. The current study examined 44 participants (22 rated high in narcissism) playing as trustors in one-shot trust games, and their electroencephalograms were recorded. Individuals high in narcissism exhibited less trust toward strangers, especially after strangers’ reciprocity. Additionally, narcissists exhibited a larger N2 following distrust and a stronger negatively-valanced difference in feedback-related negativity (dFRN) after trustee feedback. Our findings provide insights into how individuals with narcissism trust strangers. The results also shed light on the temporal course of brain activity involved in trust decision-making and outcome evaluation in individuals with narcissism.